Students Difficulties in Understanding Listening Lessons (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) - Fiza Rauzika Altasa; Cut Dara Ilfa Rahila; Muhammad Abrar Muda; Muhammad Hasyimsyah Batubara (Asosiasi Dosen Perguruan Tinggi Islam, 2023)
Listening is one of the essential skills that need to be mastered by students who want to learn English. This study concerns students' difficulties in understanding listening lessons. This research aims to describe the students' difficulties in learning to listen. The method used in this research is Preferred Reporting Items for Systematic Reviews and Meta-Analyses. This method is a process of searching the literature, while the source of portal searching literature is OJS-based journals, whether or not Sinta accredits them. The data taken are articles relating to students' difficulties in listening lessons, while the number of articles used as a reference for systematic review or meta-analysis is primarily the result of research. The articles used were 12 articles over the last two years. The results of the study show that difficulties in listening comprehension can be caused by various factors, including the knowledge and background of the listener, the clarity and quality of the spoken language, the level of attention and motivation of the listener, limited vocabulary, cognitive and language abilities, cultural and social differences, and emotional state.